ENGLISH-INDONESIAN TRANSLATION SHIFTS FOUND IN THE SUBTITLES OF THE HUNGER GAMES - -, FORTUNITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This research tries to reveal the types of translation shifts found in the subtitles of The Hunger Games and what might influence the translator of the subtitles of The Hunger Games to do shifting. This research is a qualitative research and the method used is content or document analysis. The writer uses both the English subtitle and the Indonesian subtitle in order to know what kinds of translation shifts found there. The category shift with the most occurrence is the unit or rank shift, and the category shift with the least occurrence is the class shift. Mostly, the translator does the shift since every language has its own grammar, rules and systems. The structures differ, especially for languages that come from different family of language such as English and Indonesian. Those differences can create a gap and it should be bridged by the translator by doing shift in order to avoid the unnaturalness in translation.Keywords : translation, shift, subtitles.